Determinants of Reusing Implant Contraception Through The Safari KB Program in Surakarta - Indarwati; Andriyani, Annisa; Maryatun; Handayani, Sri; Susilowati, Tri (PT Inovasi Pratama Internasional, 2024)
Purpose This research analyzes the characteristics and determinants of repeat users of Implan contraception in Surakarta. Method This is a quantitative-research using a cross-sectional survey approach with 117 purposively selected samples. Data was collected using a questionnaire that has been tested for validity and reliability using the Cronbach's Alpha formula, with a reference value of ≥ 0.07. The data was analyzed through univariate and bivariate analyses using the chi-square test and multivariate analysis with logistic regression. The analysis was developed through a three-stage backward conditional modeling process. The first stage involved screening variables that met the criteria for inclusion in multivariate analysis. The second stage analyzed variables that were significantly related to the dependent variable. In the third stage, the variables contributing the most to the dependent variable were determined. Results: In the first stage of modeling analysis, it was found that the education level variable could not be included in the multivariable analysis. In the second stage, six variables were analyzed, and only three variables showed a strong and significant relationship, which were employment status with an Odds Ratio (OR) of 3.05, parity with an OR of 4.62, and the age of the last child with an OR of 2. In the third stage, by examining the magnitude of the Odds Ratio, it was determined that the parity variable with an OR of 4.62 was the strongest variable related to the dependent variable. Conclusion; The characteristics of repeated Implan method users are working mothers, having children aged at least three years, having at least two children, being married for more than 10 years, and having both male and female children.